Cyprus Research Award–Young Researcher in the thematic area of Social Sciences and Humanities - Antoniou, Kyriakos (My University, 2026)
Award is annually given by the Cyprus Research and Innovation Foundation to one Cypriot young researcher (maximum 7 years after PhD completion) with internationally recognised research in order to support their future work and research career. See the following link: https://www.research.org.cy/en/rtdi-culture/research-award/#toggle-id-7
Keywords: Sciences